2021
DOI: 10.1186/s12886-021-01938-y
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic displacement of laser in situ keratomileusis flaps: an integrated clinical case presentation

Abstract: Background Traumatic dislocation of laser-assisted in situ keratomileusis (LASIK) corneal flaps is an uncommon postoperative complication that could occur any time after LASIK, and could be visually devastating. We evaluated the visual outcomes, corneal sensation, tear function, and dry eye questionnaire results of patients with traumatic dislocation of LASIK flaps, including one LASIK flap amputation. Methods This is a retrospective case series. S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Three cases reported epithelial ingrowth (grades 2 to 3) present at initial presentation, which resolved after flap dehiscence repair. 10,14,17 The other 3 cases reported epithelial ingrowth appearing after the initial flap repair, with one requiring a repeat procedure to resolve the ingrowth. 8 The other 2 were grade 1 epithelial ingrowths that did not require repair because they showed no progression and were not obstructing the visual axis.…”
Section: Discussionmentioning
confidence: 99%
“…Three cases reported epithelial ingrowth (grades 2 to 3) present at initial presentation, which resolved after flap dehiscence repair. 10,14,17 The other 3 cases reported epithelial ingrowth appearing after the initial flap repair, with one requiring a repeat procedure to resolve the ingrowth. 8 The other 2 were grade 1 epithelial ingrowths that did not require repair because they showed no progression and were not obstructing the visual axis.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic Flap Subluxation 32,33 Early or late traumatic flap subluxation results in blurred vision and foreign body sensation.…”
Section: Subconjunctivalmentioning
confidence: 99%
“…Flap creation using femtosecond laser allows designing flaps more personally, and many studies have proved its safety and efficiency [ 2 , 3 , 4 ]. It has been suggested that FS-LASIK behaves as good as or even better than mechanical microkeratomes in the predictability of postoperative spherical equivalent, and seems to have several advantages, but on the other hand no clear evidence of differences between the two modalities in terms of outcomes has been published [ 5 , 6 and both early and late flap-related complications have been reported with both approaches [ 7 , 8 , 9 , 10 ]. In addition, despite that femtosecond laser was a great technical breakthrough, several special complications have followed up, such as suction loss, rainbow glare, light-sensitivity syndrome, and gas-related complications [ 4 , 11 ].…”
Section: Introductionmentioning
confidence: 99%